2011
DOI: 10.1149/1.3519883
|View full text |Cite
|
Sign up to set email alerts
|

Complexing Between Additives and Ceria Abrasives Used for Polishing Silicon Dioxide and Silicon Nitride Films

Abstract: Various water soluble organic additives were used in ceria-based slurries to control both the silicon oxide and silicon nitride film removal rates. Our polish results and zeta potential data suggest that the additives with ␤-diketonatelike structures can inhibit both oxide and nitride removal rates. We propose possible complexing between the additives and the ceria abrasives might be responsible for this removal rate inhibition.Since 0.25 m technology node and beyond, shallow trench isolation ͑STI͒ has replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We also observed that the addition of ascorbic acid changed the color of the ceria slurry from white to reddish brown and made it unstable. Similar results were observed by Wang et al 54 with other chemical additives including ethylenediaminetetraacetic acid and gluconic acid and was attributed to the blocking of active Ce 3+ .…”
Section: Resultssupporting
confidence: 90%
“…We also observed that the addition of ascorbic acid changed the color of the ceria slurry from white to reddish brown and made it unstable. Similar results were observed by Wang et al 54 with other chemical additives including ethylenediaminetetraacetic acid and gluconic acid and was attributed to the blocking of active Ce 3+ .…”
Section: Resultssupporting
confidence: 90%
“…In addition, it was also proposed that the specific form of an amino acid (depending on the pKa value) plays a vital role in blocking the chemically active sites on ceria, 25 presumably Ce 3þ species, 8,9 and silicon nitride 26 surfaces. Recently Wang et al 27 proposed a model in which a chemical complex is formed between amino acids containing an additional carboxyl group and ceria abrasives to explain nitride RRs suppression. They predicted a six ligand complex between the oxygen atoms of the two carboxyl groups of the additive and cerium.…”
Section: Resultsmentioning
confidence: 99%
“…These particles were also used and described in our earlier investigations. 18,19 The oxide RRs were determined by measuring the thickness of the films before and after polishing using a Filmetrics F-20 interferometer. The RRs were calculated from the average of the change in the thickness measured at 20 points across a diameter of the wafer, and the standard deviation reported was based on the data from total of 40 locations obtained from two different polished wafers.…”
Section: Methodsmentioning
confidence: 99%